2012
DOI: 10.1002/lt.22472
|View full text |Cite
|
Sign up to set email alerts
|

Exercise capacity and muscle strength in patients with cirrhosis

Abstract: Exercise capacity and muscle strength are predictors of outcome in a number of clinical populations. Advanced liver disease is a catabolic state, and patients often have muscle wasting. However, the relationships between exercise capacity, strength, and outcomes for patients undergoing liver transplantation are poorly understood. Thirteen studies have examined the association between these parameters in patients with cirrhosis, and they have found a significant reduction in the exercise capacity and muscle str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 30 publications
3
108
0
5
Order By: Relevance
“…Recent studies showed that they develop impairment of exercise capacity and fitness [37,38] . Also reduced peak V O 2 can help identify patients at risk for mor- bidity and mortality after LT [7,39,40] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that they develop impairment of exercise capacity and fitness [37,38] . Also reduced peak V O 2 can help identify patients at risk for mor- bidity and mortality after LT [7,39,40] .…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al 15 M/F -masculino/feminino; Kg -kilograma; cm -centímetros; Kg\cm2 -quilograma por centímetro quadrado; dados descritos em média e desvio padrão; proporção e porcentagem e mediana e intervalo interquartil (P 25 -P 75 ); p -nível de significância (≤ 0,05). A força do aperto de mão e a composição corporal não foram diferentes estatisticamente entre os grupos (Tabela 3).…”
Section: Discussionunclassified
“…7 Experimental models demonstrate that the mitochondrial oxidation of fatty acids is enhanced in non-alcoholic fatty liver disease, such that increased flux through the mitochondrial tricarboxylic cycle leads to an increase in reactive oxygen species (ROS) and induction of proinflammatory mediators; furthermore, the inhibition of this flux mitigates hepatic insulin resistance, ROS and inflammation. 8 Therefore, inhibition of ROS signalling presents an attractive therapeutic opportunity. 2 In this single blind, cross-over trial, 19 NASH subjects and 19 age, gender and body mass index matched controls were randomised to 20 g dark chocolate or milk chocolate twice a day for 2 weeks, with a 1 week washout period in between.…”
Section: Acknowledgementmentioning
confidence: 99%
“…Physical activity, for example, has been demonstrated to improve QoL and outcomes in a wide range of diseases, even in cirrhotic patients. 8 In summary, while hepatitis C is a relevant (co-) factor for chronic liver disease, other measures that aim to reduce the burden of liver disease should not be overlooked.…”
mentioning
confidence: 99%